(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Online gambling games are included in one of the social deviant behaviors that exist in society, because some community groups consider gambling behavior to be something that is not good and not in accordance with applicable norms. The purpose of this study is to find out the description of the existence of online gambling in adolescents based on sociological studies. This study uses library research research methods using 7 scientific articles as references. The results of the study show that the rapid development of technology is not always used for positive things. One of the negative uses of technology is online gambling. Online gambling itself is a game that is done by risking the capital you have to get multiple returns from the invested capital. Some of the factors that encourage teenagers to do online gambling include learning outcomes, environmental factors, lack of employment, and addiction. The impact of the online gambling phenomenon, especially players, tends to lead to the negative side, including diminishing values in material values, spiritual values, moral values. so that it can lead to the emergence of behavior that deviates from social norms in the environment.